Key constraints to smallholder village chicken production and marketing systems in Centre-Nord region, Burkina Faso - Dione, Michel M.; Ilboudo, Guy S.; Alders, R.; Kagambèga, A.; Ima, S.; Ganser, C.; Boz, Z.; Knight-Jones, Theodore J.D. (International Livestock Research Institute, 2023)
Objective Chicken keeping among rural households in low-income countries like Burkina Faso provides an important source of income, nutrition, and gifts to strengthen social ties. However, the sector is hampered by high losses mostly due to diseases, limited access to farm inputs and value chain inefficiency impacting on productivity, marketing and human health. To better understand these issues, we investigated challenges faced by male and female poultry producers and other value chain actors, with emphasis given to animal health and welfare issues.